Excess Mortality as a Predictor of Mortality Crises: The Case of COVID-19 in Italy - Lidia Ceriani; Paolo Verme (Global Labor Organization (GLO), 2020)
The paper provides initial evidence that excess mortality rates by locality can be used as a statistically reliable predictor of looming mortality crises. Using recently published daily deaths figures for 7,357 Italian municipalities, we estimate the growth in daily mortality rates between the period 2015-2019 and 2020 by province. All provinces that experienced a major mortality shock in mid-March 2020 had increases in mortality rates of 100% or above already in mid-February 2020. This increase was particularly strong for males and older people, two recognizable features of COVID-19. Using panel data models, we find a strong positive and significant association between overall deaths and COVID-19 related deaths, and between early increases in mortality rates in February 2020 for any cause and the March 2020 outbreak in COVID-19 deaths. We conclude that the growth in mortality rates can potentially be used as a statistically reliable predictor of mortality crises, including COVID- 19 crises.
Keywords: 330